Nowe instytucje dla biznesu wykorzystującego sztuczną inteligencję – elementy etyczne - Sroka, Robert (Humaniora. Czasopismo Internetowe, 2024)
The aim of the article is an attempt to present the ethical elements in the newly shaped by the European Union institutions for business and, more broadly, for an economy based on advanced digital solutions, especially artificial intelligence (AI) systems. The presented research is conducted within the institutional approach in economic theory, which takes into account social and axiological elements in economic analyses. The first part presents selected negative social consequences of the business use of artificial intelligence systems. The second part contained a brief analysis of the significance of institutions in the concept of institutional economics. Then, key documents of the European Union related to the ethical aspects of AI use by businesses were introduced, especially the upcoming AI Act regulation.